Registro del águila solitaria (Buteogallus solitarius, Tschudi 1844) en la planicie costera central de Oaxaca - García-Grajales, Jesús; García-García, Gary Abner; Buenrostro-Silva, Alejandra (Instituto de Ecología, A.C., 2018)
We report the record of a solitary eagle (Buteogallus solitarius) in the municipality of Santa María Tonameca, in the central coastal plain of Oaxaca. The record was obtained through the use of a camera reflex. We considered this report as important due to the species’ demographic rarity and to recognize the places where the individuals of B. solitarius are registered in order to generate protection actions in the short to long term to improve its conservation.